214k views
2 votes
Copy and complete the steps for simplifying the expression below. Use properties to justify as many steps as possible 2d + 11 - 5d - 4 = 2d + 11 + (-5d) + (-4) = 2d + (-5d) + 11 + (-4) = d(2 +(-5)) + 11 + (-4) = -3d + 7

User Hexagon
by
4.5k points

1 Answer

3 votes

Explanation:

The given expression is :

2d+11-5d-4

It can be written as :

2d+11-5d-4 = 2d+11+(-5d)+(-4)

Taking like terms together,

= 2d+(-5d)+11+(-4)

Taking d common from above expression :

= d(2+(-5))+11+(-4)

= d(-3)+7

We know that, a(x) = ax

= -3d+7

Hence, these are the required steps.

User Amay
by
4.8k points